AMU Meeting Planned July 11–15 at Naples, Fla. (Hello World!, 1977)
A symposium on the Evolution of Mollusca will highlight the 43rd annual meeting of the American Malacological Union, Inc. (AMU) July 11-15 at Naples, Florida.